ANALISIS DAN FORMULASI STRATEGI KETERSEDIAAN AIR BERSIH DI LOKASI TRANSMIGRASI (STUDI KASUS: KACAMATAN LASALIMU SELATAN KABUPATEN BUTON) - Novita Ita Estika; Suprihatin Suprihatin; Muhammad Yani (Graduate School Bogor Agricultural University (SPs IPB), 2017)
The clean water is not always a big city’s issue. A sub-district of South Lasalimu is an example of how a clean water problem exists due to natural factor. This research work aims to assess the availability of water clean sources in a transmigration area. The based on this assessment a strategy for clean water management in the area is formulated. This research used methods of water quality analysis, Guttman scale, requirement analysis, water quantity analysis, and SWOT analysis. The research identified that water resources available in the area consist of well water, water river, and rainwater. The daily need of clean water per person was is identified as 59 Liter, so all local residents in the area require approx. 15,656 m3/year. It is necessarily important to manage water resources in order to fulfill the need of clean water. An alternative for clean water management is by utilizing rain water to secure the clean water supply. With the rainfall of about 3,681 mm/year, there would be 18,405 m3/year of clean water can be collected from the rain. There are several steps to utilize the rain water through retention basin, filtration, and gravity distribution. This research also delivers an alternative strategy for an effective water resources management which used an opportunity to minimize weakness (W-O strategy), with primary priority to ask for government support in their capacity and capability (authority) to manage water resources.